Peranan Implementasi Standar Operasional Prosedur (SOP) Meningkatkan Efisiensi dan Efektivitas Operasional pada PT. Nusatama Berkah, Tbk - Rohali, Mediana Cesyanti Ajeng; Dwiridotjahjono, Jojok (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Standard Operating Procedures (SOP) is a system designed to facilitate, streamline, and control one's work. With the existence of Standard Operating Procedures (SOP), it will make the stages in the implementation of an activity run properly and correctly, so that it can increase the efficiency and effectiveness of the company's operations. PT. Nusatama Berkah, Tbk does not yet have Standard Operating Procedures (SOP) in each department, so there is often miscommunication between employees and departments that causes the efficiency and effectiveness of the company's operations still not maximized. A study on the role of implementing Standard Operating Procedures (SOP) in improving the efficiency and effectiveness of operations at PT. Nusatama Berkah, Tbk aims to know the importance of Standard Operating Procedures (SOP) for each organization. The method used in this study is a qualitative descriptive approach with Data Collection Techniques with interviews, assistance, observation, and documentation. The results of the study show that it is necessary to recommend Standard Operating Procedures (SOP) for each department with good assistance in its production. The performance of employees has improved since the availability of Standard Operating Procedures (SOP), so the availability and implementation of Standard Operating Procedures (SOPs) for each organization or company is said to be essential for improving the efficiency and effectiveness of the Company's operations.